Efektifitas Model Pembelajaran Talking Stick dalam Pembelajaran Bahasa Indonesia - Amirudin Amirudin; Laela Yohana Kurniasih (Jurnal IAI Bunga Bangsa Cirebon, 2022)
This study discusses the effectiveness of the talking stick learning model in learning Indonesian class 2B at MI Al Washliyah Perbutulan. The study was motivated by the low learning outcomes of Indonesian in the class, the learning model that lacks innovation, causing students to be less enthusiastic in learning. This study aims to determine the effectiveness of the talking stick learning model in learning Indonesian class 2B at MI Al Washliyah Perbutulan. The research method used is qualitative research. Data collection techniques using the interview method. Sources of data in this study include primary data, namely the homeroom teacher of class 2B and secondary data, namely learning outcomes of Indonesian language subjects for grade 2B students. . The results of the data were analyzed using an analytical model, from data reduction, data presentation, and drawing conclusions and verification. The results showed that the application of learning for class 2B students at MI Al Washliyah Perbutulan before using the talking stick learning model in teaching and learning activities the teacher used various learning models, but in the Indonesian language subject there were obstacles caused by several factors, namely internal factors, namely factors within students. itself, is related to the interest and motivation of students to participate in learning activities at school. External factors are the use of learning models that are not in accordance with the material presented. Furthermore, after the application of the talking stick learning model to class 2B MI Al Washliyah Perbutulan there was a definite change compared to not using the talking stick learning model. This can be seen from the number of students who achieved a score above the KKM from a total of 27 students, only 2 students who had not achieved a score above the KKM. Abstrak Penelitian ini membahas efektivitas model pembelajaran talking stick dalam pembelajaran bahasa Indonesia kelas 2B di MI Al Washliyah Perbutulan. Kajiannya dilatar belakangi oleh rendahnya hasil belajar bahasa Indonesia di kelas tersebut, model pembelajaran yang kurang inovasi sehingga menimbulkan siswa kurang semangat dalam belajar. Penelitian ini bertujuan untuk mengetahui adanya efektivitas model pembelajaran talking stick dalam pembelajaran bahasa Indonesia kelas 2B di MI Al Washliyah Perbutulan. Metode penelitian yang digunakan adalah penelitian kualitatif. Teknik pengumpulan data dengan menggunakan metode wawancara. Sumber data dalam penelitian ini meliputi data primer yaitu guru walikelas 2B dan data sekundernya yaitu hasil belajar mata pelajaran bahasa Indonesia siswa kelas 2B. . Hasil data dianalisis menggunakan model analisis, dari reduksi data, penyajian data, dan penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa penerapan pembelajaran siswa kelas 2B MI Al Washliyah Perbutulan sebelum menggunakan model pembelajaran talking stick dalam kegiatan belajar mengajarnya guru menggunakan berbagai model pembelajaran akan tetapi pada mata pelajran bahasa Indonesia mengalami kendala yang disebabkan oleh beberapa faktor yaitu faktor internal yakni faktor dalam diri siswa itu sendiri, terkait dengan minat dan motovasi belajar siswa untuk mengikuti kegiatan belajar di sekolah. Faktor eksternal yaitu penggunaan model pembelajaran yang tidak sesuai dengan materi yang di sampaikan. Selanjutnya, setelah penerapan model pembelajaran talking stick terhadap kelas 2B MI Al Washliyah Perbutulan terdapat perubahan yang pasti dibandingkan dengan tidak menggunakan model pembelajaran talking stick. Hal ini dapat terlihat dari jumlah siswa yang mencapai nilai di atas KKM dari jumlah 27 siswa hanya 2 siswa saja yang belum mencapai nilai di atas KKM.